The Use of Code Mixing Among Circulation Division Members at Solopos Media Group in Coordinating The Events Through WhatsApp Chat - Yesiana Vianingrum; Laila Alfi Rohmaten; Winarti Winarti (LPPM Universitas Duta Bangsa Surakarta, 2022)
The development of technology in this globalization era makes everything easier and more practical. One aspect that is greatly helped by technological advances is communication. Communication is a method to connects all of human desires, that is how relationship with other was created. To establish better communication, humans use language to connect the contents of their minds in order to get harmony in a certain matter. Each country has a different language from one another, however nowadays there are many cases of a certain language being used by other countries due to the influence of the spread of culture through digital technology. People start mixing two or more languages when they speak, this phenomenon is a substation of sociolinguistics called code mixing. The use of code mixing can be found in the WhatsApp group chat of Circulation Division members at Solopos. They used code mixing in coordinating the implementation of the events they hold. This article was compiled with the aim of analyzing the types of code-mixing they have used. This article is descriptive qualitative research, the data was obtained from the WhatsApp chat of the Circulation Division at Solopos Media Group and the analysis of the data was taken from books, journals and articles related to the topic.